Role of hematopoietic cells in Mycobacterium tuberculosis infection. (September 2021) - Tamburini, Bartolo; Badami, Giusto Davide; Azgomi, Mojtaba Shekarkar; Dieli, Francesco; La Manna, Marco Pio; Caccamo, Nadia
Abstract: Tuberculosis remains one of the most significant causes of mortality worldwide and the current situation shows a re-emergence of TB due to the emergence of new antibiotic-resistant strains and the widespread of disease caused by immunodeficiencies. For these reasons, a big effort is made to improve the therapeutic strategies against Mycobacterium tuberculosis and to perform new therapeutic and diagnostic strategies. This review analyzes the various hematopoietic populations, their role and the different changes they undergo during Mycobacterium tuberculosis infection or disease. We have examined the population of lymphocytes, monocytes, neutrophils, eosinophils and platelets, in orderto understand how each of them is modulated during the course of infection/disease. In this way it will be possible to highlight the correlations between these cell populations and the different stages of tubercular infection. In fact, Mycobacterium tuberculosis is able to influence both proliferation and differentiation of hematopoietic stem cells. Several studies have highlighted that Mycobacterium tuberculosis can also infect progenitor cells in the bone marrow during active disease driving towards an increase of myeloid differentiation. This review focuses how the different stages of tubercular infection could impact on the different hematopoietic populations, with the aim to correlate the changes of different populations as biomarkers useful to discriminate infection from disease and to evaluate the effectiveness of new therapies.